The Influence of the Level of Understanding and Socialization of Taxation on Student Compliance as Prospective Personal Taxpayers - Zahra, Mutia; Sabila, Amelia; Kamila, Alya Nur (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Taxes are a source of state revenue used to finance national development and government administration. Taxes can also be considered a mandatory contribution to the state, whether owed by individual or corporate taxpayers, and are legally enforceable. However, public awareness and compliance with taxation remains low in Indonesia. Prospective taxpayers, especially students, need to be educated about taxation so that when they enter the workforce and become prospective taxpayers, they can comply with tax obligations. This study aims to determine the effect of the level of understanding and tax socialization on students’ compliance as prospective individual taxpayers. The research subjects are focused on students of Universitas Bina Sarana Informatika (UBSI), Faculty of Economics and Business, Accounting Study Program, morning class. The research method used is a quantitative method with data collection techniques through questionnaires distributed to respondents. Each statement in the questionnaire is measured using a Likert scale to determine the respondents’ level of agreement with the variables studied. The results of the study indicate that both the level of tax understanding and tax socialization have a positive and significant effect on students’ compliance as prospective individual taxpayers, both partially and simultaneously. Thus, the higher the level of understanding and the intensity of tax socialization received by students, the higher their level of compliance with tax obligations.